THE RELATIONSHIP BETWEEN SERVICE QUALITY, PERCEIVED VALUE, SATISFACTION AND BEHAVIOURAL INTENTIONS IN RAIL TRANSIT INDUSTRY - Monizaihasra Mohamed; N Alia Fahada W Ab Rahman, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Much has been written about service quality, perceived value and its impacts on satisfaction and behavioural intentions. However, little research on this perspective has been carried out in public rail transit settings in Malaysia. The aim of this study is to investigate the relationship between service quality, perceived value, satisfaction, and behavioural intentions of Mass Rapid Transit (MRT) passengers in Klang Valley, Malaysia. A survey method via structured questionnaire was employed and analysis was performed using Statistical Package of Social Science (SPSS). Perceived value for money and service quality are found to be important predictors of satisfaction and behavioural intentions among MRT passengers. Thus, the findings lend support to the means end chain theory. This study also includes a discussion, conclusions, implications, and limitations of the study.